Disinhibition-like behavior in a P301S mutant tau transgenic mouse model of frontotemporal dementia. (19th September 2016) - Przybyla, Magdalena; Stevens, Claire H.; van der Hoven, Julia; Harasta, Anne; Bi, Mian; Ittner, Arne; van Hummel, Annika; Hodges, John R.; Piguet, Olivier; Karl, Tim; Kassiou, Michael; Housley, Gary D.; et al.
Highlights: The amygdala is a major site of progressive tau pathology in P301S mutant tau-expressing TAU58/2 mice. TAU58/2 mice present with early-onset disinhibition-like behavior. Aged TAU58/2 mice are hyperactive in the open field arena. Abstract: Frontotemporal dementia (FTD) presents clinically with behavioral changes including disinhibition. Mutations in the tau-encoding MAPT gene identified in familial cases of FTD have been used to generate transgenic mouse models of the human condition. Here, we report behavioral changes in a recently developed P301S mutant tau transgenic mouse, including disinhibition-like behavior in the elevated plus maze and hyperactivity in the open field arena. Furthermore, histological analysis revealed the amygdala as a primary and early site of pathological tau deposition in these mice. Taken together, neuropathological and behavioral changes in P301S tau transgenic mice resemble features of human FTD.